Correction - Fischbach, Michel; Wühl, Elke; Schaefer, Franz (Clinical journal of the American Society of Nephrology, 2019)
Fischbach M, Wühl E, Reigner SCM, Morgan Z, Schaefer F: Efficacy and long-term safety of C.E.R.A. maintenance in pediatric hemodialysis patients with anemia of CKD. Clin J Am Soc Nephrol 13: [81-90][1], 2018. - - Because of author error, a correction has been issued for the above referenced article
Gesehen am 14.05.2020